OC-046 Acetic Acid Chromoscopy Significantly Improves Neoplasia Detection Rates as compared to Cleveland Clinic Protocol during Barrett'S Surveillance. (4th June 2013) - Bhattacharyya, R; Tholoor, S; Longcroft-Wheaton, G; Basford, P; Cowlishaw, D; Poller, D; Bhandari, P
Abstract : Introduction: Cost effectiveness of Barrett's surveillance has recently being questioned due to the low neoplasia detection rate. Acetic acid chromoscopy (AAC) has been shown to improve neoplasia detection in Barrett's oesophagus but not in surveillance population. The aim of this study is to compare the effectiveness of AAC with Cleveland clinic protocol (2 cm quadrantic) guided biopsies at detecting high risk neoplasia during Barrett's surveillance. Methods: Prospective Cohort study comparing two different Barrett's surveillance strategies. All patients who underwent Barrett's surveillance between 2008–12 were recorded on a Barrett's database. All neoplasias were independently reviewed by two GI Pathologists. Barrett's surveillance patients were randomly allocated to acetic acid chromoscopy lists (cohort B) or protocol guided biopsy (Cohort A) lists. AAC involved targeted biopsy of area of concern & 3 additional biopsies from lower, middle & top end of Barrett's. Protocol guided were taken as quadrantic biopsies every 2 cm & any visible abnormality. Fisher's exact test was used for statistical analysis. Results: N = 982 Barrett's surveillance gastroscopy between 2008–12. Median age was 66 years & Median Barrett's length was 4.5 cm (range: 1–20). Male: Female = 3.3:1 . Protocol guided Cohort A: N = 655/982(66.7%). 7/655 (1%) patients were found to have high grade dysplasia (HGD) & 3/655(0.4%) had T-1 cancers with an overall high risk neoplasia detection rate of 10/655(1.5%). Acetic acid Cohort B: N = 327/982(33.2%). 18/327(5.5%) patients were found to have HGD & 14/327(4.2%) had T-1 cancers with an overall high risk neoplasia detection rate of 32/327(9.7%). This shows a statistically significant 6.5 fold (p = 0.0001) increased detection of high risk neoplasia with acetic acid guided biopsies as compared to protocol guided biopsies in Barrett's surveillance. Conclusion: This is the first report from a large exclusively Barrett's surveillance population. Our data demonstrates that acetic acid chromoscopy significantly (6.5 fold) improves the detection of high risk neoplasia in Barrett's surveillance as compared to the current standard of 2 cm quadrantic biopsies. AAC also results in significantly less number of biopsies taken so overall it will be very cost-effective. This questions the validity of the current standard of non targeted protocol guided biopsies during Barrett's surveillance. Disclosure of Interest: None Declared